Emotional, affective and biometrical states analytics of a built environment. (May 2020) - Kaklauskas, Arturas; Abraham, Ajith; Dzemyda, Gintautas; Raslanas, Saulius; Seniut, Mark; Ubarte, Ieva; Kurasova, Olga; Binkyte-Veliene, Arune; Cerkauskas, Justas
Abstract: Personal interests constitute the emphasis of client-centered, personalized marketing, which leads to personalized client fulfillment. Current shoppers are interested in more than simply buying products and services; shoppers are also interested in the surroundings of the shopping site. Everywhere in the world, an analysis of marketing value, with rare exceptions, does not integrate criteria relevant to the emotional, affective and biometrical states, valence and arousal of potential buyers. Such parameters require assessment for implementing an accurate and more effective, client-centered marketing process. This research, which required developing the Emotional, Affective and Biometrical States Analytics of the Built Environment (VINERS) Method, provides a "big picture" of built environment neuromarketing. A multiple-criteria analysis integrated the emotional, affective and biometrical states of potential buyers and the surrounding environment (its physical, economic, social and environmental criteria). Neuro-decision and neuro-correlation matrices analysis constituted its basis. This research involved the accumulation and analysis of over 350 million remote data points, which aimed to ascertain the development of the biometrical, affective and emotional maps and sought to determine over 35, 000 of average and strong correlations. The obtained dependencies constituted the basis for calculating and graphically submitting the VINERS circumplex model of affect, which the authors of this article had developed. This model is similar to Russell's circumplex model of affect. However, now, the VINERS Method has provided supplements offering new opportunities. Determination of an integrated emotional market rental (IEMR) value, provision of digital tips and optimization of the IEMR value are made possible by the VINERS Method. Highlights: Neuro-decision and neuro-correlation matrix applications are part of this personalized, video neuromarketing research. Over 350 million anonymized data and 35, 000 average and strong correlations were examined. Obtained dependencies help in calculating and visualizing the VINERS circumplex model. Influences of emotional, affective and biometrical states on the integrated, emotional market (IEMR) value of property. Pollution influences on emotional, affective and biometrical states; all these interrelate with the IEMR value.